SYNTHESIS OF NOVEL BIS PYRAZOLONES: Life Science-Chemistry - L.K.RAVINDRANATH; KUMAR, E.V.SURESH; Y.N.SPOORTHI, K.SRIKANTH; P.PHEBE (International Journal of Life Science and Pharma Research, 2012)
The mixture of acetamide 7(a-f) and with in ethanol, and ethylacetoacetate were added and the mixture was refluxed for 10-12 hours in presence of catalytical amount glacial acetic acid to get the compounds (8a-f) in good yields. The structures of these newly synthesized compounds were characterized by 1H-NMR, Mass, IR and elemental analysis